Infant development at the age of 6 months in relation to feeding practices, iron status, and growth in a peri-urban community of South Africa - Rothman, Marinel; Faber, Mieke; Covic, Namukolo; Matsungo, Tonderayi; Cockeran, Marike; Kvalsvig, Jane; Smuts, Cornelius (MDPI, 2018)
Evidence on the association between feeding practices, iron deficiency, anaemia, stunting, and impaired psychomotor development during infancy is limited. This study assessed the association between psychomotor development with early feeding practices, growth, iron status, and anaemia. Methods: This was cross-sectional baseline data of a randomised controlled trial which included 6-month-old infants and their mothers or primary caregivers (n = 750) in a peri-urban community in the North West province of South Africa. The Kilifi Developmental Inventory and a parent rating scale were used to assess psychomotor development. Feeding practices and anthropometric measurements were based on the World Health Organisation (WHO) guidelines. Anaemia and iron status were determined by blood sample analysis.